DAMPAK TALENT MANAGEMENT DAN KNOWLEDGE SHARING TERHADAP KAPABILITAS KARYAWAN MELALUI EMPLOYEE ENGAGEMENT DI PT. BAROKAH PERKASA GRUP, KALIMANTAN TIMUR - Nilhar, Nurun Nida; Mauludin, Hanif (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
The increasing demand for skilled employees makes talent management and knowledge sharing increasingly important and strategic for every organization. This research aims to determine the effect of talent management and knowledge sharing on employee capability, with employee engagement as an intervening variable at PT. Barokah Gemilang Perkasa in Balikpapan. The research is quantitative with data collection techniques using questionnaires. Fifty eight respondents to this research were employee PT. Barokah Gemilang Perkasa. The analysis technique uses PLS-SEM, testing uses the outer and inner models. Based on the test, that there are related among talent management, employee capability, employee engagement, and knowledge sharing. However, no significant related was found between knowledge sharing and employee capability, suggesting that knowledge-sharing activities do not directly enhance employee capabilities. Keywords: talent management, knowledge sharing, employee capability, employee sharing